Recycling of Lithium Iron Phosphate (LiFePO4) Batteries from the End Product Quality Perspective - Deise F. Barbosa de Mattos; Simon Duda; Martina Petranikova (Batteries)
As efforts towards greener energy and mobility solutions are constantly increasing, so is the demand for lithium-ion batteries (LIBs). Their growing market implies an increasing generation of hazardous waste, which contains large amounts of electrolyte, which is often corrosive and flammable and releases toxic gases, and critical raw materials that are indispensable to the renewable energy sector, such as lithium. Therefore, it is crucial that end-of-life LIBs be recycled in a viable way to avoid environmental pollution and to ensure the reuse of valuable materials that would otherwise be lost. Here, we present a critical review of recent developments in the field of LIB recycling with the LiFePO4 (LFP) chemistry, which is one of the fastest-growing fields, especially in the electromobility sector. Most of the recycling methods developed are not applied industrially due to issues such as complexity, cost, or low quality of the recycled product. This last issue is rarely discussed in the literature, which motivated the creation of this review article, with emphasis on the positive electrode recycling by the direct method and on the quality of the resynthesized LFP in terms of electrochemical performance.